National survey on the use of telepsychology in the work of psychologists in Serbia - Djurić Jočić, Dragana; Blažanin, Barbara; Dukanac, Vesna; Pavlović, Viktor; Pavličić, Nevenka (Vojnosanitetski pregled, 2025)
Background/Aim. In recent decades, telepsychology has gradually developed due to the increasing availability of digital technologies. However, its expansion was led by the pandemic and the introduction of social distancing rules. The aim of this study was to determine the level of computer and internet use by psychologists in Serbia in their everyday work. Methods. A hybrid research design was employed, combining survey methodology with content analysis. The survey consisted of 70 questions related to the use of digital technology in the practice of psychologists. The national survey included 340 graduate psychologists of both sexes and all age categories. The participants worked in various regions of Serbia and covered nearly all areas of psychological practice, including healthcare, education, industry, the military, and private practice. Results. The questions addressed to psychologists when a respondent is sent for tests assessment most often related to personality exploration, diagnostic/neuropsychological assessments, and psychotherapy-related evaluations. In the total sample, as many as 51% of psychologists in Serbia conducted online therapy, while a significantly smaller number of respondents (17%) performed test assessments via the Internet. In assessments, the most frequently used tests were domestically produced and have been in use for a long time, while a smaller number of psychologists used new psychological instruments. The survey revealed that younger psychologists and those from Belgrade valued telepsychology more positively compared to older psychologists and those living and working in other areas. The therapeutic orientation of the respondents was not a significant factor in assessing the success of telepsychology. Conclusion. The paper provides an overview of the current situation in the area of personality assessment and shows that the use of digital technology and telepsychology in Serbia is more developed than the professional regulations and education of psychologists regarding this modality. For the widespread application of telepsychology in the work of psychologists, it is necessary to introduce topics related to this specific modality into the curricula of university courses, both globally and in Serbia.